Postępowanie o dyspensę w sprawach super rato - Dullak, Kazimierz (Ius Matrimoniale, 2003)
The sacramental marriage is indissoluble from the beginning. Yet still important for the marriage is consummating it by conjungal act in a human manner. In case if, for any reason it hasn’t been consummated, then one or both parts have the right to request a dispensation super rato, addressed to the pope. After the thorough research according to the strict regulations whether the marriage in question hasn’t been consummated, and whether there is real and relatively important reason for dissolution, the pope can grant this grace. By this act both parts, provided that there’s no other impediment, can contract a new marriage .